2013
DOI: 10.1111/bcp.12110
|View full text |Cite
|
Sign up to set email alerts
|

Histamine‐induced vasodilatation in the human forearm vasculature

Abstract: AIMTo investigate the mechanism of action of intra-arterial histamine in the human forearm vasculature. METHODSThree studies were conducted to assess changes in forearm blood flow (FBF) using venous occlusion plethysmography in response to intra-brachial histamine. First, the dose-response was investigated by assessing FBF throughout a dose-escalating histamine infusion. Next, histamine was infused at a constant dose to assess acute tolerance. Finally, a four way, double-blind, randomized, placebo-controlled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…While most of the classical histamine-dependent effects in allergic reactions are H 1 receptor–mediated [ 54 ], H 2 receptors are involved in the associated vasodilator responses [ 28 , 50 , 54 , 55 ]. Thus, in studies on rat mesenteric arteries and rabbit aortae, histamine-induced dilatations are mediated by H 2 receptors [ 28 , 34 ]; likewise, in humans, relaxations to exogenous histamine of isolated uterine arteries are prevented by H 2 antagonists [ 55 ], as are histamine-induced increases in forearm blood flow [ 50 ]. Histamine-induced NO release in porcine endothelial cells is mediated by H 2 receptors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the classical histamine-dependent effects in allergic reactions are H 1 receptor–mediated [ 54 ], H 2 receptors are involved in the associated vasodilator responses [ 28 , 50 , 54 , 55 ]. Thus, in studies on rat mesenteric arteries and rabbit aortae, histamine-induced dilatations are mediated by H 2 receptors [ 28 , 34 ]; likewise, in humans, relaxations to exogenous histamine of isolated uterine arteries are prevented by H 2 antagonists [ 55 ], as are histamine-induced increases in forearm blood flow [ 50 ]. Histamine-induced NO release in porcine endothelial cells is mediated by H 2 receptors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in dogs and cats have reported that injection of histamine into femoral vein causes a systemic fall in blood pressure as measured from femoral artery 14 16 . Further, administration of histamine into brachial vein has shown to produce veno-dilation and increased forearm blood flow in humans 17 . The above works by far, describe the effects of histamine only on BP, due to its presence in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between the two amine pathways is still not fully understood, however histamine may impact expression of the enzyme ornithine decarboxylase (ODC), a key step in polyamine synthesis [ 61 63 ]. Histamine is a prominent vasoactive substance, helping regulate blood-flow and vascular tone [ 64 , 65 ]. It is well established that the control of blood flow is impaired in ageing with significant decrease in flow and microvascular perfusion to the muscle in response to nutritive stimuli [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%